Determinants of clinical outcome in patients with moderate/severe Graves' orbitopathy undergoing treatment with parenteral glucocorticoids: a retrospective study - Le Moli, Rosario; Naselli, Adriano; Costanzo, Gabriele; Piticchio, Tommaso; Tumino, Dario; Pellegriti, Gabriella; Frasca, Francesco; Belfiore, Antonino (Frontiers in Endocrinology, 2024)
Background Graves' orbitopathy (GO) occurs in approximately 25-40% of patients with Graves’ disease (GD). High levels of anti-thyrotropin receptor antibodies (TRAbs), smoking habit, sex, older age, longer duration and amount of hyperthyroidism or hypothyroidism are well-recognized risk factors for the occurrence, severity and clinical course of GO. Oxidative stress (OX) has recently been shown to play a role in the pathogenesis of GO, and several clinical conditions related to OX have been investigated regarding the presentation and severity of GO. Aim We aimed to evaluate the impact of clinical conditions related to oxidative stress on the outcome of intravenous glucocorticoid (ivGCs) therapy in a cohort of patients with active moderate to severe GO (AMS-GOs) treated at a single institution. Methods We retrospectively studied a series of patients with AMS-GOs who were treated with ivGCs from January 2013 to May 2022. GO clinical evaluation was performed at baseline and at 6 (W6), 12 (W12) and 24 (W24) weeks after starting ivGCs by the seven-point clinical activity score (CAS) alone and by overall clinical criteria (CI) according to the European Group of Graves’ Ophthalmopathy (EUGOGO). Total cholesterol and calculated LDL cholesterol (LDLc), triglyceride, body mass index (BMI), diabetes status, history of hypertension (HoH), smoking status, age and sex were used as covariates for the clinical outcome of GO to ivGCs. Results and conclusions LDLc and HoH negatively and independently modulated the response of AMS-GOs to ivGCs. Notably, slightly elevated LDLc levels (> 130 mg/dl) reduced the response of orbital soft tissue to ivGCs, whereas more elevated LDLc levels (from 175 mg/dl to 190 mg/dl) and HoH were associated with poorer clinical response of eye motility and proptosis.